Synergy between erosion-corrosion of steel aisi 4140 covered by a multilayer ticn / tinbcn, at an impact angle of 90° (2013)
The aim of this work is the study of the effect of corrosion erosion on wear for [TiCN / TiNbCN] n multilayer coatings on AISI4140 steel substrates. We have grown [TiCN/TiNbCN] n multilayered via reactive RF (radio frequency) magnetron sputtering technique inwhich systematically the bilayer period (Λ) and the bilayer number (n were varied), maintaining the total thickness of the coatings constant(~ 3 μm). The multilayers were evaluated and compared for corrosion, erosion and erosion-corrosion at an impact angle of 90º in a solutionof 0.5 M NaCl and silica which simulates a marine environment, analyzing the effect of the number of bilayers on the corrosion resistanceof these coatings. Polarization curves were conducted at rest potential. After the polarization experiments the specimens were analysed byscanning electron microscopy. The results show good performance of the multilayer systems in dynamic corrosion systems and erosioncorrosion,furthermore the enhancement of wear is due to the fact that the polarizations curves move towards areas where current densitiesdecrease by increasing the bilayer number.